Occupational stress in Remotely Piloted Aircraft System operators. (25th April 2019) - Phillips, A; Sherwood, D; Greenberg, N; Jones, N
Abstract: Background: Although there is currently little research data to support the contention, concerns have been raised about possible traumatic stressors inherent to Remotely Piloted Aircraft System (RPAS) operator roles. Factors such as exposure to visually traumatic events compounded by long working hours and blurred boundaries between military and civilian life have been cited as potential stressors. Robust research into the well-being of RPAS operators is scarce and mostly samples US personnel. Aims: To provide mental health and well-being data relating to UK RPAS operators. Methods: UK RPAS operators completed mental health questionnaires to assess levels of post-traumatic stress disorder (PTSD), anxiety and depression symptoms, alcohol use and occupational functioning. Respondents were also asked about work patterns. Results: Forty-one per cent of the sample reported potentially hazardous alcohol use. Ten per cent met psychiatric symptom criteria for moderate or severe anxiety, and 20% for moderate depressive symptoms. While there were no cases of probable PTSD, 30% of the sample reported sub-clinical PTSD symptoms likely to impair occupational functioning. Overall, 70% of the sample reported that psychological symptoms significantly impaired their functioning. Conclusions: Compared to UK military sub-groups, RPAS operators were not at increased risk of mental health problems. However, a high proportion of the sample reported significant functional impairment, which has not been explored in other comparable studies. The most frequently highlighted work-related stressors were timing of RPAS work and operator shift patterns.